2011
DOI: 10.2466/05.25.pms.113.5.395-408
|View full text |Cite
|
Sign up to set email alerts
|

Attack Efficacy in Volleyball: Elite Male Teams

Abstract: The goal was to identify performance indicators predicting attack efficacy in volleyball's game phase denominated Complex II, i.e., the counter-attack. 28 games from the 2007 Men's World Cup were analyzed. Attack efficacy was predicted by three primary variables: Attack tempo, Attack type, and Number of blockers. Power attack and Attack tempo 1 increased the probability of an Attack point. The supremacy of Attack tempo 3 and the high frequency of Two blockers and Three blockers reflected the difficulty of effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
45
0
31

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 19 publications
12
45
0
31
Order By: Relevance
“…These results are in agreement with other studies 6,7,12,18 , which showed the importance to perform powerful attack to score point. Although tips avoid attack error and powerful attacks increase error possibility, these are necessary for the overlay to defensive systems, which are increasingly better structured 24,25 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are in agreement with other studies 6,7,12,18 , which showed the importance to perform powerful attack to score point. Although tips avoid attack error and powerful attacks increase error possibility, these are necessary for the overlay to defensive systems, which are increasingly better structured 24,25 .…”
Section: Discussionsupporting
confidence: 83%
“…Thus, the middle attacker plays an important role because, among spikers, he is responsible for attacking most of the fastest balls, i.e., the first time balls 7 . Studies of volleyball game analysis show, regardless of game situations, that attack has association with the quality of execution of the other fundamentals 11,12,13 . In this context, there is a relationship between reception quality and the attack effect 14,15 ; the tempo of attack, the attack type and opposition faced with the attack effect 7,9 and the relationship between reception quality and the attack effect or between attack velocity and attack effect 5,14,16 .…”
Section: Introductionmentioning
confidence: 99%
“…A 28 , bem como restringe o tempo disponível para a estruturação defensiva adversária 36 . Neste sentido, é possível inferir que o jogo de voleibol de alto nível do sexo masculino emana levantamentos cada vez mais velozes para a conquista do ponto e posterior vitória no set e jogo.…”
Section: Discussionunclassified
“…Observou-se que não houve a utilização de ataques de 1º tempo e que os pontos obtidos após este tipo de receção foram reduzidos. A literatura nesta área mostra que há associação dos ataques mais rápidos com o ponto de ataque e do jogo mais lento com a continuidade do jogo e o erro do ataque (6,10,11,13,34) . (28) , sendo que receções de baixa qualidade dificultam a distribuição do levantador e se correlacionam com o erro do ataque (44) .…”
Section: Resultsunclassified
“…Assim, a qualidade da receção interfere diretamente nos procedimentos de jogo subsequentes e, principalmente, na estratégia do levantador (1,28,45) . Complementarmente a isso, o ataque realizado a partir da zona 4 mostra correlação com o aumento da incidência de bloqueios duplos (3) , que pode ser evidenciado ou apresentar condições limitadas de finalização em função da qualidade na receção (8,11,33) .…”
Section: Resultsunclassified